2017
DOI: 10.1105/tpc.16.00865
|View full text |Cite
|
Sign up to set email alerts
|

CAMTA-Mediated Regulation of Salicylic Acid Immunity Pathway Genes in Arabidopsis Exposed to Low Temperature and Pathogen Infection

Abstract: Arabidopsis thaliana calmodulin binding transcription activator (CAMTA) factors repress the expression of genes involved in salicylic acid (SA) biosynthesis and SA-mediated immunity in healthy plants grown at warm temperature (22°C). This repression is overcome in plants exposed to low temperature (4°C) for more than a week and in plants infected by biotrophic and hemibiotrophic pathogens. Here, we present evidence that CAMTA3-mediated repression of SA pathway genes in nonstressed plants involves the action of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(182 citation statements)
references
References 42 publications
9
168
1
Order By: Relevance
“…Salicylic acid immunity is repressed by CAMTA1–CAMTA3 at moderate temperatures, but derepressed under prolonged coldness or pathogen challenge (Du et al ., ; Kim et al ., ). An N‐terminal domain of CAMTA3 alone is sufficient to repress SA‐related genes, but its repression is relieved through intramolecular interaction with the C‐terminal CaM‐binding domain during cold‐induced immunity (Kim et al ., ). Massive immune activation in camta3‐ knockout plants (at 19–21°C) led to the notion that CAMTAs act as negative regulators of immunity (Du et al ., ; Nie et al ., ).…”
Section: Environmental Effects On Plant Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Salicylic acid immunity is repressed by CAMTA1–CAMTA3 at moderate temperatures, but derepressed under prolonged coldness or pathogen challenge (Du et al ., ; Kim et al ., ). An N‐terminal domain of CAMTA3 alone is sufficient to repress SA‐related genes, but its repression is relieved through intramolecular interaction with the C‐terminal CaM‐binding domain during cold‐induced immunity (Kim et al ., ). Massive immune activation in camta3‐ knockout plants (at 19–21°C) led to the notion that CAMTAs act as negative regulators of immunity (Du et al ., ; Nie et al ., ).…”
Section: Environmental Effects On Plant Immunitymentioning
confidence: 99%
“…NPR1 independence of salt/drought tolerance, despite HSFA1 requirement therein, points to cold-specific engagement of the NPR1-HSFA1 module, which does not require SA, defense-related TGAs, NPR1 sumoylation, ABA or CBF1. Further studies will be required for the mechanisms underlying NPR1/HSFA1-mediated freezing tolerance and their possible involvement in cold-induced immunity (Kuwabara & Imai, 2009;Kim et al, 2017).…”
Section: Low Temperaturementioning
confidence: 99%
“…Therefore, pathogen‐induced SA accumulation plays a key role in mediating the establishment of cold and heat tolerance induced by pathogen infection. In our previous work, SA was evidenced to be required for cold‐activated defense response (Kim et al, ; Wu et al, ). Taken together, SA is suggested to be a phytohormone underlying the interaction between defense response and abiotic stress such as cold and heat in plants.…”
Section: Discussionmentioning
confidence: 94%
“…In overwintering grasses, some pathogenesis‐related proteins, including endochitinases, β‐1,3‐glucanases, and thaumatin‐like proteins, were synthesized after exposed to low temperatures (Seo et al, ), and it was evidenced that cold acclimation induced the accumulation of SA, a classical disease resistance phytohormone, in Arabidopsis , wheat, and grape berry (Kim, Park, Gilmour, & Thomashow, ; Miura & Furumoto, ). Furthermore, Kim et al () detected increased disease resistance in cold acclimated Arabidopsis plants. Their work indicated that the activation of disease resistance is associated with the release of CAMTA transcription factors‐mediated repression of SA biosynthesis (Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation